Amantadine in Treatment of Dysthymia-The Pilot Case Series Study - Marek Krzystanek; Ewa Martyniak; Artur Pałasz; Katarzyna Skałacka; Artur Chwalba; Piotr Wierzbiński (MDPI AG, 2023)
Dysthymia is a common chronic mood disorder in which isolated symptoms of depression persist for at least 2 years. Despite the many medications recommended for the treatment of dysthymia, no recommendations have yet been made for the treatment of patients who fail to achieve clinical improvement. This justifies attempts to identify second-line drugs for the treatment of dysthymia. In an open and naturalistic case study, five patients diagnosed with dysthymia in whom at least one antidepressant treatment was ineffective were treated with amantadine. In the age- and gender-matched external control group, patients were treated with sertraline at 100 mg/day. Depressive symptoms were assessed using HDRS-17. Two men and three women were treated with 100 mg amantadine for 3 months with 3-5 months follow-up. After 1 month of treatment with amantadine, a significant reduction in the intensity of depressive symptoms was achieved in all patients, and the clinical improvement increased over the next 2 months of treatment. No deterioration in well-being was observed in any patient after discontinuation of amantadine. The effect of amantadine treatment was comparable to that of sertraline treatment in patients with dysthymia who improved with this drug. The present study indicates that amantadine is an effective and well-tolerated drug in the treatment of dysthymia. Amantadine may be associated with a quick improvement in symptoms in the treatment of dysthymia. Treatment with this drug seems to be associated with good tolerability and persistency of the therapeutic effect after the discontinuation of the treatment.